Resistance Level of Crocidolomia pavonana Against Profenofos Synthetic Insecticide and its Susceptibility To Azadirachta Indica Seed Extract - Danar Dono; Yogas Dwi Pratiwi; Safri Ishmayana; Djoko Prijono (CROPSAVER, 2018)
This research was conducted to know resistance level of Crocidolomia pavonana  to a profenofos synthetic insecticide and to know susceptibility of C. pavonana  to Azadirachta indica seed extract. The experiment using two bioassay methods, dry film method and feeding method.  Field population of C. pavonana  obtained from 3 villages in Lembang district i.e.Cibogo, Cikole and Kayu Ambon village. The standard insect has been maintenance more than 20 generations in the laboratory as a comparison.  The result of the experiment indicated that population of C. pavonana  form Cikole, Cibogo and Kayu Ambon village were resistant to profenofos insecticide with resistance ratio (RR)  was low (1< RR ≤ 5).  Resistance Ratio of C. pavonana  from the third village were 4.69 and 4.83; 1.02 and 1.1 and 1.16 and 1.9 respectively (dry film and feeding method). The value of the resistance ratio was greater through the feeding assay compared to the contact assay. This indicated that the mechanism of C. pavonana resistance was likely to occur mainly in the digestive tract of insects. Enzime activity of the different sample population of C. pavonana indicated variation in their activity. This was indicated that every sample from different field could develop different mechanism of resistance. The toxicity study of A. indica  seed extract to C. pavonana  indicate that the field population of C. pavonana  from the third village was susceptible to seed extract of A.indica  with value RR of less than one point. Therefore seed extract of A. indica  could be used as alternative control against C. pavonana  which resistant to profenofos synthetic insecticide.Keywords: Resistance mechanism, Resistance ratio, Synthetic insecticide, Botanical insecticide